2008
DOI: 10.1002/bjs.6327
|View full text |Cite
|
Sign up to set email alerts
|

Importance of extrasphincteric mechanisms in the pathophysiology of faecal incontinence in adults with a history of anorectal anomaly

Abstract: Faecal incontinence in adult patients with ARA is related to various pathophysiologies. Structural integrity of the anal sphincters is a major factor, but extrasphincteric mechanisms, notably rectal sensory function, may be as important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…In conclusion, although many authors [24,25] state that patients with imperforate anus have significant disruption of IAS and EAS, these injuries were investigated in few cases. Anorectal manometry and 3D-EAUS are validated, highly sensitive, and specific examinations for defining injuries to the anal sphincter complex.…”
Section: Discussionmentioning
confidence: 94%
“…In conclusion, although many authors [24,25] state that patients with imperforate anus have significant disruption of IAS and EAS, these injuries were investigated in few cases. Anorectal manometry and 3D-EAUS are validated, highly sensitive, and specific examinations for defining injuries to the anal sphincter complex.…”
Section: Discussionmentioning
confidence: 94%
“…The coexistence of constipation and incontinence is recognized as being much higher in association with specific clinical pathologies, including spinal cord injury [93], and congenital anorectal anomaly [94]. However, a detailed description of these conditions is beyond the scope of this review.…”
Section: Coexistent Constipation and Fecal Incontinence In Adultsmentioning
confidence: 99%
“…Although the sphincter dysfunction is considered the most important factor in AI, sensitivity and rectal adaptation plays a role in it (24). The response of EAS to the rectal distension is crucial to maintain the continence and is closely related to the sensorial function and rectal compliance (21).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the sustained squeeze pressure must be considered as the time interval in which the pressure stays > 50% of the maximal pressure (10). The normal values vary in the different studies being indicated with the stationary technique values from 32 seconds (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in males and 24 seconds (20)(21)(22)(23)(24)(25)(26)(27)(28) in females (7).…”
Section: Introductionmentioning
confidence: 99%